한약과 양약의 병용 치료를 통한 약인성 간손상 치험례 1례 - 이은형(Eun Hyoung Lee); 김상헌(Sang Heon Kim); 박상은(Sang Eun Park); 송수진(Su Jin Song); 서창운(Chang Un Seo); 이용태(Yong Tae Lee); 김원일(Won Il Kim) (동의생리병리학회지, 2007)
A liver is responsible for drug metabolism in a body. 10% of all medicine side effects lead to liver injury. Herb medicine is not an exception to this rule but all Herb medicines do not lead to liver injury absolutely. As for two times of occurrence of the drug induced liver injury during treatment of a CVA patient, we gave him Herb medicines in conjunction with Western medicines and Western medicines alone for each case. We meet with the result that giving the patient Herb medicines in conjunction with Western medicines reduces the duration of decreasing AST, ALT level as compared with giving him Western medicines alone. So we are now reporting the result.